Some adhesins of avian pathogenic Escherichia coli (APEC) isolated from septicemic poultry in Brazil - Knöbl, Terezinha (2006)
Three hundred and fifty strains of E. coli isolated from septicemic poultry from seven states of Brazil were examined for presence of nine adhesion-encoding genes, hemagglutination and adherence to chicken tracheal cells (in vitro). Analysis of the strains by colony hybridization tests demonstrated that 93.7% of the isolates were fim +, 17% pap+ and 5.7% were sfa+. The mannose sensitive fimbriae occur with similar frequency in APEC isolated from all Brazilians states, while significant differences among pap and sfa genes distributions were observed. The results showed that 0.85% and 0.28% of APEC were positive for genes that encoded enteroaggregative adhesins and EPEC adherence factor, respectively. None of APEC was positive for DA, afa, Bfp and Eae probes. The adherence to chicken tracheal cells showed 96% positive strains, while hemagglutination assays showed 26.5% of the isolates were mannose sensitive and 21.7% were mannose resistant.